2017
DOI: 10.1249/mss.0000000000001336
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Not Sedentary Time, Predicts Dual-Energy X-ray Absorptiometry–measured Adiposity Age 5 to 19 Years

Abstract: Purpose To examine the associations among physical activity (PA), sedentary time (SED), and TV viewing (TV) with fat mass (FAT) and visceral adipose tissue mass (VAT) from childhood through adolescence (5–19 years). Methods Participants in the Iowa Bone Development Study (n = 230 males and 233 females) were examined at ages 5, 8, 11, 13, 15, 17 & 19 years. Accelerometers measured moderate- or vigorous-intensity PA (MVPA; min/day), light-intensity PA (LPA; min/day), and SED (h/day). Parent-proxy report (5 & 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 33 publications
2
40
1
Order By: Relevance
“…5 Therefore, children with CHD are more prone to increased arterial stiffness, but the role of physical activity on arterial stiffness has not been previously investigated. We extend prior reports by demonstrating that physical activity volume may help modulate Low physical activity increases overweight and obesity risk, 19 and these factors adversely contribute to arterial stiffness in children. 20 Sakuragi et al 6 CHD may be more causally attributed to physical activity levels, rather than established anthropometric determinants of arterial stiffness.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…5 Therefore, children with CHD are more prone to increased arterial stiffness, but the role of physical activity on arterial stiffness has not been previously investigated. We extend prior reports by demonstrating that physical activity volume may help modulate Low physical activity increases overweight and obesity risk, 19 and these factors adversely contribute to arterial stiffness in children. 20 Sakuragi et al 6 CHD may be more causally attributed to physical activity levels, rather than established anthropometric determinants of arterial stiffness.…”
Section: Discussionsupporting
confidence: 84%
“…Low physical activity increases overweight and obesity risk, and these factors adversely contribute to arterial stiffness in children . Sakuragi et al found that BMI, waist circumference, and % body fat were all independently and positively associated with arterial stiffness in healthy children, and more so than exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…6 In fact, the majority of the studies objectively measuring sedentary time found no relationship with BMC or BMD in pediatric populations, which concurs with our findings. 6,28 It should be noted that the association of hepatic fat content with BMD was independent of physical activity in the current report.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, experimental evidence supports a complex network between the bone, the liver, and adipose tissue regulating bone remodeling, liver metabolism, and glucose homeostasis through the secretion of pro-/anti-inflammatory cytokines and hormones. 26 On the other hand, physical activity, 27 particularly MVPA, 28,29 has positive effects on bone metabolism and bone accrual in childhood and adolescence. Sedentary behavior, on the contrary, is related to higher risk of cardiovascular disease and mortality, 30 while its influence on bone health is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Data used in the current prospective cohort analyses were collected as part of the longitudinal Iowa Fluoride (IFS) and Iowa Bone Development Studies (IBDS), Clinical Trial Registration: NCT03547128, which investigated fluoride exposures, dietary intakes, oral health, and bone measures [ 9 , 10 , 11 , 12 , 13 ]. Mothers ( n = 1882) were recruited at the time of their children’s births for participation in the IFS, and IFS participants active at age 5 (approximately 800) were invited to participate in the IBDS.…”
Section: Methodsmentioning
confidence: 99%